2006
DOI: 10.1097/01.sla.0000217667.55939.64
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Subjective and Objective Results of Laparoscopic and Conventional Nissen Fundoplication

Abstract: The effects of LNF and CNF on general state of health and objective reflux control are sustained up to 5 years after surgery and the long-term results of LNF and CNF are comparable. A substantial minority of patients in both groups had a second antireflux operation or took antisecretory drugs, although the use of those medications did not appear to be related to abnormal esophageal acid exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
82
1
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(91 citation statements)
references
References 43 publications
(35 reference statements)
1
82
1
7
Order By: Relevance
“…13 In addition intraluminal impedance monitoring enables quantification of both acid and weakly acidic reflux and proximal reflux events. 14 In this study we used high resolution esophageal manometry combined with pH and impedance monitoring to evaluate late (14-year) objective outcomes in a subset of patients enrolled in a prospective randomized trial of anterior 180˚ partial vs. Nissen fundoplication.…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition intraluminal impedance monitoring enables quantification of both acid and weakly acidic reflux and proximal reflux events. 14 In this study we used high resolution esophageal manometry combined with pH and impedance monitoring to evaluate late (14-year) objective outcomes in a subset of patients enrolled in a prospective randomized trial of anterior 180˚ partial vs. Nissen fundoplication.…”
Section: Introductionmentioning
confidence: 99%
“…Nissen fundoplication restores the third function and provides excellent reflux control. [1][2][3] However, it delivers a supracompetent valve which can impair the first two functions. Three meta-analyses have demonstrated that Nissen fundoplication is followed by a significant incidence of troublesome postfundoplication side effects, including troublesome postoperative dysphagia and gas related problems.…”
Section: Introductionmentioning
confidence: 99%
“…It is effective in reducing gastro-oesophageal reflux, both acid and nonacid. 95 The mechanisms through which fundoplication reduces reflux are complex and incompletely understood. Currently, it is believed that three mechanisms may play a role.…”
mentioning
confidence: 99%